2016
DOI: 10.1136/bmjresp-2016-000144
|View full text |Cite
|
Sign up to set email alerts
|

Yield of EBUS-TBNA for the diagnosis of sarcoidosis: impact of operator and cytopathologist experience

Abstract: BackgroundStudies have reported a high diagnostic yield of endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) for the diagnosis of sarcoidosis. We sought to review the yield of EBUS-TBNA for the diagnosis of sarcoidosis at our institution over time, and examine factors that may influence this yield.MethodsPatients who underwent EBUS-TBNA for suspected sarcoidosis between December 2008 and November 2011 were identified. EBUS was performed without rapid on-site evaluation (ROSE) of samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 22 publications
4
23
0
Order By: Relevance
“…Another point to consider is the experience of the bedside cytopathologist. It has been previously reported by Navasakulpong et al that the experience of the cytopathologist can influence the results of EBUS‐TBNA, which is also applicable to the results of ROSE . In our study, ROSE was reported as non‐diagnostic initially in 12/30 patients by the bedside pathologist, which changed to diagnostic in elective review later by the senior experienced cytopathologist.…”
Section: Discussionsupporting
confidence: 59%
“…Another point to consider is the experience of the bedside cytopathologist. It has been previously reported by Navasakulpong et al that the experience of the cytopathologist can influence the results of EBUS‐TBNA, which is also applicable to the results of ROSE . In our study, ROSE was reported as non‐diagnostic initially in 12/30 patients by the bedside pathologist, which changed to diagnostic in elective review later by the senior experienced cytopathologist.…”
Section: Discussionsupporting
confidence: 59%
“…Furthermore, a granulomatous reaction in mediastinal LNs is not an uncommon finding in cancer patients because it may be related to a tumor‐induced hypersensitivity reaction . Other causes of granulomatous inflammation, such as subclinical sarcoidosis, should also be considered in the differential diagnosis . Our finding of granulomatous inflammation in cancer patients is consistent with other studies finding that granulomatous inflammation in hilar or mediastinal LNs is one of several causes of PET positivity …”
Section: Discussionsupporting
confidence: 90%
“…Under the guidance of an ultrasound probe, EBUS‐TBNA can target a suspicious mediastinal LN and obtain tissue samples for morphological evaluation . EBUS‐TBNA demonstrates much higher sensitivity and specificity than conventional transbronchial needle aspiration and/or other biopsy procedures for the assessment of mediastinal and hilar LNs …”
Section: Introductionmentioning
confidence: 99%
“…Different from our current study, the cumulative yield per lymph node was not analyzed in the study by Sun et al [21], as the number of needle passes per lymph node was not precisely defined. A few investigators have suggested that the use of EBUS-TBNA for multiple lymph nodes rather than a single lymph node increases the diagnostic yield [6, 22], but this remains controversial [21, 23]. Our study indicated no difference in diagnostic yield between 1 and 2 lymph nodes.…”
Section: Discussionmentioning
confidence: 41%
“…Some investigators have assessed the number of passes or lymph nodes required as a secondary endpoint [5, 6, 21-23]. In an early study on the usefulness of EBUS- TBNA for diagnosing sarcoidosis, Garwood et al [5] reported a diagnostic yield of 85%, and the cumulative yield exceeded 80% at 5 passes.…”
Section: Discussionmentioning
confidence: 99%